2016
DOI: 10.1590/1678-4162-8624
|View full text |Cite
|
Sign up to set email alerts
|

Primeiro registro de Amblyomma geayi (Acari: ixodidae) em preguiça (Bradypus variegatus) no estado do Acre, Amazônia Ocidental: relato de caso

Abstract: RESUMOO Amblyomma geayi é um carrapato da família Ixodidae, encontrado principalmente em mamíferos e aves silvestres de regiões tropicais da América do Sul. Descreve-se a ocorrência de um carrapato ixodídeo da espécie A. geayi, encontrado em uma preguiça (Bradypus variegatus) proveniente do Parque Zoobotânico da Universidade Federal do Acre, Rio Branco, Acre, Amazônia Ocidental. Palavras-chave: carrapatos, Ixodídeos ABSTRACT Amblyomma geayi is a tick of the Ixodidae family found primarily in mammals and wild b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…According to literature data (Aragão, 1936;Guimarães et al, 2001;Souza et al, 2016) (Canestrini, 1888). According to Labruna et al (2005), previous reports of A. incisum from the Amazonian region require confirmation, as they could be misidentified with Amblyomma scalpturatum Neumann, 1906or Amblyomma latepunctatum Tonelli-Rondelli, 1939; hence, we do not consider valid the report by Aragão (1936) of A. incisum in Acre.…”
Section: Discussionmentioning
confidence: 99%
“…According to literature data (Aragão, 1936;Guimarães et al, 2001;Souza et al, 2016) (Canestrini, 1888). According to Labruna et al (2005), previous reports of A. incisum from the Amazonian region require confirmation, as they could be misidentified with Amblyomma scalpturatum Neumann, 1906or Amblyomma latepunctatum Tonelli-Rondelli, 1939; hence, we do not consider valid the report by Aragão (1936) of A. incisum in Acre.…”
Section: Discussionmentioning
confidence: 99%
“…In Southern America, Brazilian zoo-animal infection cases have been connected to the following tick species of the Amblyomma and Rhipicephalus genera: A. dubitatum , A. calcaratum , A. aureolatum , A. sculptum or R. sanguineus in Southeastern regions of Brazil [ 21 ]. More Amblyomma species were collected from animals kept in zoos located in Northern and Northwestern Brazil: A. dissimile , A. variatum , A. geayi , A. longirostre , A. goeldii , A. humerale , A. naponense or A. nodosum [ 29 , 30 ]. In Europe, Ixodes ricinus is the most common tick found in zoos and wildlife parks or farms [ 20 , 31 , 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…In 2016, Souza et al (2016) reported, for the first time, parasitism of a three-toed sloth (Bradypus New records of ticks (Acari: Ixodidae) infesting wild birds in a forest fragment in Acre, Brazilian Amazon variegatus) from the Zoobotanical Park of the Federal University of Acre by a male individual of Amblyomma geayi Neumann, 1899. Gruhn et al (2019) conducted a study in Rio Branco, Acre, intending to investigate the presence of bacteria of the genus Rickettsia in ticks collected from free-living capybaras (Hydrochoerus hydrochaeris).…”
Section: Introductionmentioning
confidence: 99%